A Case of Sub-acute Combined Degeneration of the Spinal Cord with Associated Pernicious Anaemia - Bhuiyan, AA; Dash, SK; Shahriar, SMH; Nahid, F; Arefin, S (Pulse, 2014)
Aim and Objective Vitamin B12 deficiency disease, specially associated with pernicious anaemia is a relatively rare disease in the developing countries. Patients with B12 deficiency may present with hematological, gastro-intestinal and neuro-psychiatric manifestations. Here we discuss a case of a fifty five-year-old lady presented with sub-acute combined degeneration of the spinal cord. Case presentation A fifty five year old female was admitted in Neurology ward in Apollo Hospitals, Dhaka from OPD for progressive quadriparesis with tingling in the hands and feet. She had no associated visual, bulbar symptoms, sphincter incontinence or memory impairment. Investigation revealed mild anaemia, macrocytosis on peripheral blood picture, low Vitamin B12 level with megaloblastic changes in bone marrow examination. Anti-Intrinsic factor antibody and anti-parietal cell antibody was not done, as it is not available here. MRI of dorsal spine shows T2 hyper-intense lesions in the posterior cord. GI Endoscopic biopsy revealed chronic atrophic gastritis. Conclusion We presented this case because of its relatively uncommon occurrence in our country. Sub-acute combined degeneration of spinal cord associated with dietary deficiency is common in Indian sub-continent. High index of suspicion is needed for its early diagnosis as delay in treatment can lead to poor neurological recovery. DOI: http://dx.doi.org/10.3329/pulse.v5i1.20193 Pulse Vol.5 January 2011 p.57-60